2019
DOI: 10.1111/cid.12786
|View full text |Cite
|
Sign up to set email alerts
|

Labial soft tissue contour dynamics following immediate implants and immediate provisionalization of single maxillary incisors: A 1‐year prospective study

Abstract: Background Soft tissue dynamics in the esthetic zone are gaining increasing attention in recent years. Emerging intraoral scanning technology allows easier capture of soft tissue contours. Purpose To quantitatively assess the time‐dependent contour alterations of labial soft tissue following single immediate implants and immediate provisionalization (IIPP) in maxillary incisors via intraoral scanning. Materials and Methods This was a prospective cohort study. Thirty eligible consecutive patients were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 35 publications
1
49
0
3
Order By: Relevance
“…When it comes to time of implant placement, Arora and Ivanovski found a similar horizontal buccal ridge resorption for immediate (0.61 mm) and delayed (0.72 mm) implant placement [34]. Tian et al [55] reported a mean buccal horizontal reduction of 0.62 mm, 1 year after immediate implant placement and grafting of the residual jump gap combined with immediate provisionalisation. These figures are lower compared to the results of our study (0.889 mm) but can be explained by the absence of bone grafting and the difference in socket anatomy and size (molar vs anterior).…”
Section: Discussionmentioning
confidence: 95%
“…When it comes to time of implant placement, Arora and Ivanovski found a similar horizontal buccal ridge resorption for immediate (0.61 mm) and delayed (0.72 mm) implant placement [34]. Tian et al [55] reported a mean buccal horizontal reduction of 0.62 mm, 1 year after immediate implant placement and grafting of the residual jump gap combined with immediate provisionalisation. These figures are lower compared to the results of our study (0.889 mm) but can be explained by the absence of bone grafting and the difference in socket anatomy and size (molar vs anterior).…”
Section: Discussionmentioning
confidence: 95%
“…During a one-year follow-up period, the labial soft tissue contour showed a continuous alteration. The total mean change was 0.62 mm, mainly in the first three months [40]. The PES value before treatment was 11.16, and at one year of follow-up, 10.25.…”
Section: Discussionmentioning
confidence: 87%
“…Digital models of mandibular bone, extraction socket (a digital model of hard tissue containing the entire extraction socket), the M2M, and root complex of the M3M after coronectomy were segmented and saved in stereolithography le format for further analyses in GeoMagic™ Studio 12 (3D Systems, Rock Hill, SC, USA) [19]. Models of mandible bone with clear anatomic markers were applied for registration according to the "Best-Fit Alignment" algorithm [25,26]. Hence, the relative migration and variation at two times (baseline and Po.6 m) could be visualized directly.…”
Section: Construction and Measurement Using The Digital Model 231 Rmentioning
confidence: 99%